Challenges and Recent Progress on Silicon‐Based Anode Materials for Next‐Generation Lithium‐Ion Batteries. Issue 6 (14th April 2021) - Zhang, Chengzhi; Wang, Fei; Han, Jian; Bai, Shuo; Tan, Jun; Liu, Jinshui; Li, Feng
Abstract : The electrode materials are the most critical content for lithium‐ion batteries (LIBs) with high energy density for electric vehicles and portable electronics. Considering the high abundance, environmental friendliness, low cost, high capacity, and low operation potential of silicon‐based anode, it has been intensively studied as one of the most promising anode materials for high‐energy LIBs. However, the widespread application of silicon anode is impeded by the poor electrical conductivity, large volume variation, and unstable solid–electrolyte interfaces films. In the past decade, significant efforts have been demonstrated to tackle these major challenges toward industrial applications. Herein, the focus is on combining with advanced structure like nanostructure and composite with other materials, exploring various new polymer binders, improving electrolyte, different prelithiation strategies, and Si/graphite design to meet commercialization requirements, particularly summarized the progress on areal capacity, initial Coulombic efficiency, and cost. Finally, the guidelines and trends for practical silicon electrodes are presented based on the recent reports. Abstract : Silicon‐based anode endows high capacity and low operation potential. However, silicon is impeded by the poor electrical conductivity, large volume variation, and unstable solid–electrolyte interfaces films. Herein, the focus is on combining with advanced structure, binders, electrolyte, prelithiation strategies, and Si/graphite design to meet commercialization requirements, particularly introduced the progress on areal capacity, initial Coulombic efficiency, and cost.